Achieving a more usable World Wide Web. - Hanson VL; Richards JT (Behaviour & Information Technology)
Over the last few years, we have built and tested two systems designed to make Web content more accessible for people with limited vision and dexterity. The first system, based on content transcoding via a proxy server, possessed several attractive features but proved to be unacceptably complex, error prone, and slow. The second system, based on client-side transformations, worked well enough to be broadly deployed. We report here on lessons learned and on the current state of the research effort. We review the two systems, discuss their strengths and weaknesses, and examine how the second system is being used.